Trust Your Gut: The Association of Gut Microbiota and Liver Disease - Ridda Manzoor; Weshah Ahmed; Nariman Afify; Mashal Memon; Maryam Yasin; Hamda Memon; Mohammad Rustom; Mohannad Al Akeel; Noora Alhajri (Microorganisms, 2022)
The gut microbiota composition is important for nutrient metabolism, mucosal barrier function, immunomodulation, and defense against pathogens. Alterations in the gut microbiome can disturb the gut ecosystem. These changes may lead to the loss of beneficial bacteria or an increase in potentially pathogenic bacteria. Furthermore, these have been shown to contribute to the pathophysiology of gastrointestinal and extra-intestinal diseases. Pathologies of the liver, such as non-alcoholic liver disease, alcoholic liver disease, cirrhosis, hepatocellular carcinoma, autoimmune hepatitis, viral hepatitis, and primary sclerosing cholangitis have all been linked to changes in the gut microbiome composition. There is substantial evidence that links gut dysbiosis to the progression and complications of these pathologies. This review article aimed to describe the changes seen in the gut microbiome in liver diseases and the association between gut dysbiosis and liver disease, and finally, explore treatment options that may improve gut dysbiosis in patients with liver disease.